Risk Factors for Blood Transfusion in Revision Total Hip Arthroplasty for Mechanical Failure - Lee, Ryan; Lee, Danny; Fassihi, Safa; Zeller, Zachary; Stake, Seth; Kappa, Jason; Webber, Michael; Thakkar, Savyasachi C.; Pandarinath, Rajeev (The Journal of Hip Surgery, 2020)
Revision total hip arthroplasty (rTHA) is associated with significant intraoperative blood loss requiring transfusion. Given that blood transfusions increase the risk of numerous complications, efforts should be made to determine which patients are at high risk of transfusion and optimize them appropriately. This study aimed to identify independent risk factors associated with blood transfusion in patients undergoing rTHA for mechanical failure. A multi-institutional surgical registry was queried for all patients who underwent rTHA for mechanical failure from 2005 to 2016. Patients were divided into transfused and nontransfused cohorts and underwent univariate analysis for differences in demographic features, preoperative comorbidities, and operative variables. Multivariate regression models were generated to elucidate independent risk factors associated with perioperative blood transfusions. A total of 8,469 rTHA patients met inclusion and exclusion criteria, of which 1,863 (22.0%) received blood transfusions within 72 hours postoperatively. On multivariate logistic regression analysis, age ≥ 65 years (odds ratio [OR] 1.313; p < 0.001), female gender (OR 1.465; p < 0.001), insulin-dependent diabetes mellitus (OR 1.503; p = 0.003), chronic obstructive pulmonary disease (COPD; OR 1.307; p = 0.030), hypertension (OR 1.359; p < 0.001), hematologic disorders (OR 1.565; p < 0.001), preoperative blood transfusions (OR 3.851; p < 0.001), systemic sepsis (OR 2.277; p = 0.003), functional dependence (OR 1.416; p = 0.003), open wounds/wound infections (OR 2.878; p < 0.001), and operations lasting at least 175 minutes (OR 4.841; p < 0.001) were all significant independent risk factors for blood transfusions. Obesity (body mass index [BMI] ≥ 30 kg/m2; OR 0.818; p = 0.001), smoking history (OR 0.800; p = 0.014), and isolated acetabular component revision (OR 0.730; p < 0.001) were associated with a decreased risk of blood transfusion. Older age, female gender, lower BMI, absence of smoking history, functional dependence, insulin-dependent diabetes mellitus, hypertension, revision of the femoral component, preoperative transfusion, hematologic disorders, sepsis, open wounds/wound infections, COPD, and longer operative time were all independent risk factors for blood transfusions in rTHA performed for mechanical failure. By identifying these risk factors, clinicians can identify and optimize high-risk patients to minimize blood transfusion requirements, thereby reducing the risk of transfusion-associated complications in this patient population.
Keywords: blood transfusion; revision total hip arthroplasty; total hip arthroplasty